Seismic signal processing - Chew, William Wei Liang. (2010)
The progress of the Seismic Signal Processing Project is summarized in this report. The main objective of this project is to build a seismic signal processing data acquisition system to facilitate the development of signal processing algorithms. Seismic processing involves many applications such as earthquake, oil exploration, footsteps and vehicle detection. The second part of the project presents the development of signal processing algorithms. This includes detailed study and verification on the feasibility of homomorphic deconvolution technique on seismic processing on footsteps and vehicle movement detection.